1994
DOI: 10.1063/1.110858
|View full text |Cite
|
Sign up to set email alerts
|

Ion implantation of porous silicon

Abstract: We have investigated the properties of light-emitting porous silicon after ion implantation and successive annealing through continuous-wave photoluminescence (CWPL) and time dependent photoluminescence (TDPL) spectroscopies. Implantation was performed with phosphorus, boron and silicon ions of different doses and energies. Low dose dopant implantation keeps or even increases the CWPL intensity and increases the TDPL decay time. High dose dopant implantation and silicon self-implantation reduce the CWPL intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The resistivity of the reference PSi layer formed by electrochemical etching of n-Si(100) was about 1.5 MΩ·cm. Peng et al (1994) have found that the resistivity of the boron implanted samples was Downloaded by [United Arab Emirates University ] at 03:40 27 June 2016 always much higher than the reference sample (e.g., 45.7 MΩ·cm for a dose of 10 13 cm -2 ) but it decreased when increasing the implantation dose. Phosphorous implanted samples, however, had a lower resistivity than the reference sample (e.g., 0.9 MΩ·cm for a dose of 10 13 cm -2 ) and the resistivity decreased with increasing implantation dose.…”
Section: Ion Implantationmentioning
confidence: 97%
See 1 more Smart Citation
“…The resistivity of the reference PSi layer formed by electrochemical etching of n-Si(100) was about 1.5 MΩ·cm. Peng et al (1994) have found that the resistivity of the boron implanted samples was Downloaded by [United Arab Emirates University ] at 03:40 27 June 2016 always much higher than the reference sample (e.g., 45.7 MΩ·cm for a dose of 10 13 cm -2 ) but it decreased when increasing the implantation dose. Phosphorous implanted samples, however, had a lower resistivity than the reference sample (e.g., 0.9 MΩ·cm for a dose of 10 13 cm -2 ) and the resistivity decreased with increasing implantation dose.…”
Section: Ion Implantationmentioning
confidence: 97%
“…As it is known, PSi layers have high resistivity and the decrease of the resistance is necessary in order to obtain effective electroluminescent structures based on PSi. Peng et al (1994) studied PSi implanted by silicon, boron, and phosphorus at an energy of 150, 75, and 170 keV, respectively. The implantation dose varied from 10 12 to 10 15 cm -2 .…”
Section: Ion Implantationmentioning
confidence: 99%
“…The effects of implantation on the luminescence of porous silicon have been studied by several authors. Barbour et al [3] and Peng et al [4] have shown that implanting a small dose of dopant atoms such as B and P maintains or even increases the continuous-wave photoluminescence intensity and increases the time-dependent photoluminescence decay time, while high dose dopant implantation quenches the photoluminescence efficiency. In addition, blue emission was not reported by the authors.…”
Section: Introductionmentioning
confidence: 98%
“…Some approaches, such as high temperature annealing [1], boiling-water treatment [2], ion implantation [3,4] etc., have been attempted in order to reduce the size of the silicon nanocrystals to further enlarge the band gap of Si and to increase the emission intensity. Ion implantation is one of the good candidates for nanocrystal formation due to its compatibility with Si device processes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in order to improve the PL efficiency and stability of the luminescent PS, lots of research efforts have been made by using the passivation process of PS surface by Ge [6], Au [7], ZnSe (CdSe) [8], and diamond-like carbon (DLC) [9], and various formation conditions [10], the HF aqueous solution containing Fe ions [11], the thermal annealing process [12], the surface oxidation process [13], and the impurity incorporation through doping [14] or ion implantation [15] on PS layer. But it was very difficult to achieve simultaneously both the high PL efficiency and the invariable PL wavelength in PS layer with the reported process above.…”
Section: Introductionmentioning
confidence: 99%